PENDAMPINGAN DAN SOSIALISASI SERTIFKASI HALAL GRATIS (SEHATI) BAGI UMKM - Cahya Febrina, Sindy; Yuniriyanti, Eny; Yuni Prihantono, Eko; Adi Fiansyah, M.Widhi (Universitas Kadiri, 2024)
Increasing awareness of halal products is the main key in supporting the growth of MSMEs. Halal certification not only creates a competitive advantage for MSMEs but also increases consumer trust in halal products. This activity aims to assist MSMEs in obtaining halal labels and socialize the importance of halal certification for products. This activity was attended by the Halal Center Cendekia Muslim (HCCM), MSMEs RW 08, Tanjungrejo Village, Sukun District, Malang City, and students. The results of this activity are 1) participants understand the knowledge about halal, and the importance of halal; 2) participants know the halal products used; 3) MSMEs get halal certification to increase product sales.